Isolation of some microorganisms from Iraqi patients with chronic maxillary sinusitis. - Zeiny, Sarmad M.; Al-Salloum, Suhaila M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Maxillary sinusitis is one of the most common infections of humans. Sinusitis can be defined as an inflammation of the membrane lining of any sinus, especially one of theparanasal sinuses.Objective: To determine the causative microorganisms of chronic maxillary sinusitis.Patients: Forty five chronic sinusitis patients were involved in the present study.Methods: Sampling method were sinus specimens (aspiration or injection aspiration).Results: Haemophilus species, Streptococcus pneumoniae (S.pneumoniae) and Moraxella catarrhalis (M.catarrhalis) were the most frequent isolates; in addition Penicillium andCladosporium species were isolated from some chronic sinusitis patients.Conclusion: Chronic sinusitis could be caused by either bacterial species or by fungal species; most bacterial isolates were Haemophilus species followed by S.pneumoniae andM.catarrhalis. The incidences of chronic sinusitis were more at patients age (20-29 years) old groups.